Intellectual or developmental disabilities and curative female breast cancer treatment: A population-based retrospective cohort studyLay summary - Rebecca L. Hansford; Brooke Wilson; Rebecca Griffiths; Alyson L. Mahar (Breast)
Background: Adults with intellectual or developmental disabilities (IDD) diagnosed with breast cancer are more likely to die than those without IDD. Differences in breast cancer treatment among individuals with and without IDD could contribute to survival disparities. We compared breast cancer treatment receipt among adults with and without IDD. Methods: A population-based retrospective cohort study was conducted using administrative data. We included adult females diagnosed with stage I-III breast cancer in Ontario (2007–2018). IDD status was identified using an established algorithm. We estimated associations between IDD and surgical resection, adjuvant chemotherapy, and radiation using cause-specific hazards models in four distinct cohorts determined by stage and treatment eligibility. Unadjusted and adjusted hazard ratios (HR; adjusted for region, rurality, previous cancer, stage and year of diagnosis) with 95 % confidence intervals are reported, accounting for the competing event of death. Cancer subtype was not adjusted for as about 25 % of participants were missing this information. Effect modification by age, stage and comorbidity was explored. Results: The four cohorts included 100,679 (IDD = 369), 12,526 (IDD = 57), 60,279 (IDD = 167), and 7891 individuals (IDD = 22), respectively. Relative to those without IDD, people with IDD were less likely to receive surgical resection (HR = 0.84; 0.76–0.94), breast conserving surgery (HR = 0.69; 0.60–0.80), adjuvant chemotherapy (HR = 0.49; 0.32–0.74), and radiation (HR = 0.58; 0.46–0.73). People with IDD were as likely to receive mastectomy (HR = 1.13; 0.97–1.33). Significant interactions by age and IDD were detected for receipt of mastectomy (interaction p-value = 0.03) and breast conserving surgery (interaction p-value = 0.02). Conclusions: Research to understand treatment decision-making, the accessibility of breast cancer treatment, and to examine potential pathways to improve receipt of guideline-recommended care are needed to inform targeted improvements in care delivery.